207. THE EVOLUTION OF THE PERIOPERATIVE ENHANCED RECOVERY PROTOCOL IN ESOPHAGEAL SURGERY DURING 10 YEARS. (24th September 2022) - Yan, Maria; Ruchkin, Dmitry
Abstract: The perioperative enhanced recovery protocol routinely uses in esophageal surgery. It acquired new aspects which were adapted to reduce the rate of morbidity and mortality. Esophagectomy still remains a high-risk operation, which carries out in high-volume centers on patients with significant comorbidities. It challenges the multidisciplinary team to personalize approach to create a safe recovery after surgery. The objective of the study is to show the aspects of evolution of the protocol after esophageal surgery. A total 393 patients with benign and malignant esophageal diseases underwent esophagectomy with simultaneous reconstruction between December 2012 and December 2021. The median age was 59 years (47;67), females were 39, 7% and males—60, 3%. The prevalence of the patient with nutritional deficiency was 20% (BIM < 18.5) and ASA score III-IV—66, 9%. The tranthoracic and transhiatal esophagectomy were used for 42, 2% and 57, 8% of patients with the reconstruction by gastric pull up (92, 1%), colon conduit (6, 4%), jejunal loop interpostion with gastric pull-up 1% and with colon conduit 0, 5%. 169 patients (43%) had postoperative complications, while 28, 9% of them had one complication and 3, 6% more than 4 complications at the same time. The prevalence of complications: pneumonia—8, 2%, atrial dysrhythmia requiring intervention—7, 7%, pulmonary embolism—1%, acute renal failure requiring dialysis—1, 5%. The anastomotic leak occured in 5, 4% patients and conduit necrosis—in 2, 8% (2, 3% extensive) patients. The prevalence of patients required repeated surgery was 6, 4%. The rate of severe complications (>IIIb- Clavien-Dindo) was 14, 4%. Median postoperative day was 9 (8;11). The postoperative mortality rate 1, 8%. The aspects of the perioperative enhanced recovery protocol were modified to complicated surgery with simultaneous resection of other organs, esophagogastrectomy or reconstruction by combined conduit with jejunal loop with early oral feeding and rapid recovery. The decade-long experience of the evolution of the perioperative enhanced recovery protocol has led to the development of the personalized approach to the patients with significant comorbidities that allowed reducing the incidence of postoperative complications and mortality after esophagectomy.